Path Analysis on the Biopsychosocial Determinants of Infertility among Reproductive Aged Women in Surakarta, Central Java - Zauma, Luthfia; Budhiastuti, Uki Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background: